FILM PENDEK TENTANG MENDUKUNG ODHA UNTUK SISWA SMA ANTARTIKA SURABAYA - Ahmad Fahri (Universitas Airlangga, 2018)
Discrimination to PLWHA (People Living With HIV&AIDS) still happen today. The lack of information about PLWHA and HIV&AIDS being caused to discrimination. So it need a health promotion which aim to increase people's knowledge. Media which used determine success of information delivery to students in Antartika high school Surabaya, which is close to high frequency of PLWHA place in Surabaya. This research is implemented using Research and Development (R&D) design which aiming to develop a short film to promote health. The research use quesionnaire which given to 69 students. And an interview aiming to get characteristic of the targets. Beside it also conducted an expert review to get a feedback for the prototype and short film media that have been developed.Students of Antartika high school need to get information about PLWHA discrimination, HIV transmission, and the medium that bring HIV. Short flm that has been produced is adapted by students characteristic that loving Indonesian films with action genre and using bahasa. The film media has duration within 5 minutes and have a message that we must supporting PLWHA, not avoid them, using morale approach that aim targeting group that watching the film get a morale value. Keyword: health promotion media, PLWHA, discrimination, film